Pemahaman Tukang Jamu Mengenai Kebermanfaatan Jamu Kunir Asem di Yogyakarta - Muhamad Jalil (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Turmeric tamarind is one of the traditional drinks that is quite familiar in the eyes of the community. The younger generation needs to be introduced to the legacy of traditional herbal medicine, so that its existence is maintained. There is still an assumption that herbal medicine is an outdated traditional drink. The purpose of this study was to determine the knowledge of herbal medicine sellers about the benefits of turmeric acid. This study uses a qualitative method. Retrieval of data by means of documentation, interviews, and documentation. Data were analyzed in a descriptive qualitative manner. Furthermore, information is obtained about additional ingredients added in the manufacture of tamarind turmeric. Turmeric tamarind in the view of herbal medicine sellers can provide many benefits as an antibiotic, fresh body, and overcome cough colds. Additional tamarind herbal remedies include lemongrass, brown sugar, salt, cloves, and sweet.